Análisis granulométrico de sedimentos y dinámica fluvial en la cuenca del río Lorohuasi (Cafayate, Salta) - Quintero, Daniela Irene (2021)
River processes have the ability to modify all terrestrial systems. The release of components, their transport and deposition as sediments by water have important environmental consequences, many of which can be deteriorating or irreversible. Arid regions are susceptible to water erosion, since the mere existence of water flow is exceptional and the common situation is its extreme speed, which is combined with the spatio-temporal variability of sediment transport. In this context, the objective was to analyze the dynamics of sediment transport in the Lorohuasi river basin, Cafayate, Salta, in the middle sections of the Alisal and Colorado tributaries, throughout the Lorohuasi river and the river mouth in the Santa María river, between the years 2016 and 2020. In 30 plots of 1 m2 located in 14 study sites, 30 samples of medium and fine sediments were collected in the active channel of the rivers. At each site, the width and slope of the channel was measured, as well as the flow, with the granulometric data of the medium sediments, were constructed accumulated frequency graphs and tables of statistical parameters (mean, median, mode, standard deviation, asymmetry and kurtosis), in order to characterize and analyze the distribution of the granulometric fractions along the river courses, evaluate the sedimentation dynamics and characterize the transport agent. The results show that in general lines, the mean granulometry of all the analyzed material transported in the Lorohuasi river basin is mean sand (phi 1.15), with mean-median-mode in the same fraction, the distribution is mesokurtic, symmetric and the material is poorly selected. The sediment is transported majorly by saltation in the Colorado and Alisal rivers, and by saltation and/or suspension in the Lorohuasi river. It is concluded that the physical characteristics of the basin and anthropic activities influence the granulometry of the analyzed sediments, especially in the lower basin, and that rehabilitation techniques in affected riverbank areas could restore their functionality and protect the river system.